Comparison of Small Incision Lenticule Extraction Surgery With and Without Cyclotorsion Error Correction for Patients With Astigmatism. Issue 6 (June 2019) - Chen, Pei; Ye, Yiming; Yu, Na; Zhang, Xiaoying; He, Jiexu; Zheng, Hua; Wei, Han; Zhuang, Jing; Yu, Keming
Abstract : Purpose: To evaluate the add-on effect of manual cyclotorsion error correction by the cornea-marking method over standard small incision lenticule extraction (SMILE) surgery in astigmatic eyes. Methods: Consecutive patients (84) who had preoperative myopic astigmatism of −0.75 diopters (D) or more and were seeking surgical refractive correction by SMILE surgery during July 2017 to August 2017 were included in this study and randomized to treatment with standard SMILE surgery (S group: 30 eyes) or cyclotorsion compensated SMILE surgery (CC group: 54 eyes). The visual acuity and refractive outcomes were analyzed preoperatively and postoperatively. Refractive astigmatic changes were analyzed by the Alpins method. Results: The S and CC groups were comparable preoperatively regarding age, manifest spherical equivalent, and manifest refractive cylinder. The mean position-related cyclotorsion degree in the enrolled astigmatic eyes for the S and CC groups was 1.7 ± 2.2 degrees (ranging from 0 to 10 degrees) and 2.19 ± 1.74 degrees (ranging from 0 to 10 degrees), respectively. The mean cylinder was −1.67 ± 0.54 D versus −1.72 ± 0.71 D preoperatively. Six months after treatment, the surgical outcomes in the CC group were significantly better than those of the S group, with a postoperative corrected distance visual acuity of −0.07 ± 0.07 versus 0.016 ± 0.13. A vector analysis of astigmatism also yielded better outcomes in the CC group. However, these 2 groups were statistically similar in spherical equivalent. Conclusions: SMILE surgery combined with cyclotorsion error compensation yielded a significant improvement in surgical outcomes regarding safety, efficiency, and predictability for patients with astigmatism.